THE SCIENTIFIC AND PRACTICAL IMPORTANCE OF USING FOREIGN EXPERIENCES IN THE ORGANIZATION AND MANAGEMENT OF EDUCATIONAL PROCESSES (American Journal of Pedagogical and Educational Research, 2024)
In this article, we discuss the scientific and practical importance of using foreign experiences in the organization and management of educational processes. Studying and summarizing advanced work experience of developed countries is one of the important tasks of the school. This article serves to enrich the practical activities and theoretical conclusions of public educational institutions and school employees.